Influence of spacer materials on underlapped and self-aligned UTBB SOI nMOSFET - Teixeira, Fernando F.; Agopian, Paula G.D. [UNESP]; Martino, Joao A. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
In this paper the influence of spacer material (S13N4, S1O2 or vacuum) on Ultra Thin Body and Buried Oxide (UTBB) SOI nMOSFET for underlapped and self-aligned drain engineering devices are studied by bi-dimensional numerical simulations. It is observed that the short length underlap devices are more influenced by spacer material. On the other hand, self-aligned does not present much spacer material dependence for the studied dimensions.
Keywords: self-aligned; SOI; Spacer; Ultra Thin Body and Buried Oxide; underlap